The Impact of COVID-19 on Formal Firms : Micro Tax Data Simulations across Countries - Bachas, Pierre; Brockmeyer, Anne; Semelet, Camille (World Bank, Washington, DC, 2020)
How is the COVID-19 pandemic affecting firm profits and tax payments in developing countries? This paper uses administrative corporate tax records from 10 low- and middle-income countries around the world to provide plausible estimates. Modeling the lockdown-triggered revenue shock with simple and transparent assumptions, the analysis predicts that less than half of all firms will remain profitable by the end of 2020, about 5-10 percent of the formal aggregate annual payroll will be lost, and firm exit rates will double. As a result, it is expected that tax revenue remitted by the corporate sector will fall by at least 1.5 percent of baseline gross domestic product. Differences in sectoral composition and firms' cost structures generate heterogeneity in the results across countries: wage subsidies are less effective in low-income countries and government revenue losses are smaller.